Cellular Reconstruction of the Rectal Mucosa during surgical Treatment of Familial Adenomatosis of the Colon: 12 Years after the First Experience of Introduction into Clinical Practice - D. V. Vyshegorodtsev; A. M. Kuzminov; S. I. Achkasov; E. A. Kogan; V. Yu. Korolik; G. T. Sukhikh (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To study long-term results of surgical treatment of patients with familial adenomatous polyposis (FAP) with the cell reconstruction of the rectal mucosa.Materials and methods. 57 FAP patients were subjected to treatment, which involved colproctectomy, the preservation of the lower rectal ampulla, mucosectomy and the reconstruction of the mucosa by cell transplantation. Endoscopic monitoring was carried out, with the endoscopic observation covering the period of 19–120 months (median — 44.3 months). Morphological and immunohistochemical studies were conducted. The long-term functional results of treatment (anorectal manometry (profilometry)) were studied. The patients were surveyed using the SF-36 questionnaire to monitor the quality of their life.Results. Our results show that the use of cell transplantation leads to the reconstruction of the rectal mucosa over a fairly short time: in 44/57 (77.2 %) patients, the endoscopic picture corresponded to the unchanged rectal mucosa 4 weeks after the surgery. In 13/57 (22.8 %) patients, a complete mucosal reconstruction was achieved 8–12 weeks after the surgery. The absence of polyp growth in the preserved part of the rectum was observed. Late complications developed only in 5 (9.4 %) patients. Good functional results (acceptable frequency of defecation, lack of signs of anal incontinence and nocturnal defecation) were observed in 48/53 (90.6 %) patients. The quality of life was at a fairly high level in 90.6 % of patients.Conclusion. The proposed method of FAP treatment allowed the immediate and long-term treatment results to be improved significantly.